PELAKSANAAN PERATURAN DAERAH PROVINSI RIAU NOMOR 10 TAHUN 2014 TENTANG PELAYANAN PUBLIK DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Putriyanda, Diennissa; Haryono, Dodi; Firdaus, Emilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Regional Regulation (Perda) of Riau Province No. 10 of 2014 concerning about Public Service as a legal basis for the region in implementing regional autonomy related to administrative matters relating to mandatory public service. In Riau Province, one of the problems in public service is in health field. Public service health concerns with many people’s lives and direcly related to the social aspects of humanity. The hospital is an institution of public service for people who use services in the health field. RSUD Arifin Ahmad is owned by Riau Province which organized of health services. However, at this time, health care at RSUD Arifin Ahmad of Riau Province is still can not fulfill the satisfaction of the service reception.RSUD Arifin Ahmad of Riau Province performs the functions of health care should be able to fulfill the satisfaction of the comunity as recipients of services because it has intimation of service that states the ability to carry out the service standarts are assigned and the legislation in force; one of which is a Provincial Regulation of Riau Province No. 10 of 2014 about Public service, which is under and responsible to the Governor of Riau Province.Key Words: Regional Regulations – Public Services – Hospitals